2022
DOI: 10.1016/j.wasman.2021.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Waste recycling policies and Covid-19 pandemic in an E-DSGE model

Abstract: Among the environmental problems we have still to face in the 21st century, waste production and management are particularly pressing. Despite policy efforts, waste volumes are still increasing worldwide and landfilling remains the main disposal option in several parts of the world. Together with the huge environmental impacts of the large amounts of waste landfilled, it would be possible to save enormous amounts of resources improving reuse and recycle options. The impact of the COVID-19 outbreak has been sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…Additionally, results showed that throughout the span of the pandemic and as of now, the amount of non-recyclables being produced has significantly increased. A similar finding was reported by Argentiero et al [34]. This is an overarching finding that is further explored through the rest of the discussion.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Additionally, results showed that throughout the span of the pandemic and as of now, the amount of non-recyclables being produced has significantly increased. A similar finding was reported by Argentiero et al [34]. This is an overarching finding that is further explored through the rest of the discussion.…”
Section: Resultssupporting
confidence: 87%
“…Another study done by de Blasio & Fallon [56] offered more valuable insight reporting that policymakers need to create incentives to rationalize plastic waste chains that are currently highly fragmented. Argentiero et al [34] corroborates this idea, reporting the positive effects of both incentive based and behavioral policy changes such as information/educational campaigns. All of these are practical policies that can create small steps in reducing the damage to the environment and public health caused by the pandemic.…”
Section: Policiesmentioning
confidence: 84%
See 2 more Smart Citations
“…In Italy, in particular, 34% of waste is still landfilled, while 28% is sent for recycling, 18% is composted, and 21% is burned in waste-to-energy plants. Moreover, it should also be considered that recent analyses of the impact of the COVID-19 outbreak on waste cycle management [21,22] have shown an actual increase in the amount of non-recycled materials due to sanitary needs and new safety consumption practices. Therefore, the increase in the quantity of recycled waste, in accordance with EU requirements [1], requires the constant updating of Waste Management Plans implemented by regional administrations [23].…”
Section: Introductionmentioning
confidence: 99%